(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3bHd HGH GdbGa hGdTjf heG HYOgeG HebOGQ hQbJjf aYjd HGdfUH UhJ GdeGA hGdbSi CjVkG KjGH jDJi HgG ef eUQ hai GdMOjK HGY GHf eSYhO OQGge GdQHGYi (B: (3aYdd HGdaJM s
(3GdfSNI HgG MhGTs
(3JJab ai BNQgG eY BNQ GdLRA GdKGfi ef fSNI NRGfI GdEeGe jMji Hf eMeO ai HYV GdCdaGXs
(3eged GdfbW CMjGfkGs
(3cJHJ GdYfhGfGJ HGdMeQI Ydi MhGTjgG ebGHdGJ HgG JbWjY s
(3HChQGbgG HYV GdGVWQGH ai GdJQJjH s
(3HOGNdgG HYV GdChQGb HNW eZGjQs
Keywords: (3GddZIs